Carnegie's maid (Books on Tape, Sourcebooks Landmark, 2018)
Clara Kelley is not who they think she is. She's not the experienced Irish maid who was hired to work in one of Pittsburgh's grandest households. She's a poor farmer's daughter with nowhere to go and nothing in her pockets. But the other woman with the same name has vanished, and pretending to be her just might get Clara some money to send back home. If she can keep up the ruse, that is. Serving as a lady's maid in the household of Andrew Carnegie requires skills he doesn't have, answering to an icy mistress who rules her sons and her domain with an iron fist. What Clara does have is a resolve as strong as the steel Pittsburgh is becoming famous for, coupled with an uncanny understanding of business, and Andrew begins to rely on her. But Clara can't let her guard down, not even when Andrew becomes something more than an employer. Revealing her past might ruin her future -- and her family's.--Provided by Publisher.